Analisis Kontribusi Penerimaan Pajak Bumi Bangunan Dan Bangunan Wilayah Desa Pasir Awi Terhadap Pendapatan Asli Daerah Kabupaten Tangerang - Martina Marince Bian Mali (Universitas Katolik Soegijapranata, Semarang, 2023)
Martina Marince Bian Mali, Analysis of the Receipt of Land and Building Tax Contributions for the Pasir Awi Village Area to the Regional Original Income of Tangerang Regency, under the guidance of Mr. Erion, SE, MM., M.Phil. The aims of this study were (1) to analyze the Contribution of Land and Building Tax Revenue from the Pasir Awi Village Area to the Regional Original Revenue of Tangerang Regency, and (2) to analyze the level of effectiveness of the contribution of Land and Building Tax Revenue from the Pasir Awi Village Area to the Regional Original Income (PAD) ) Tangerang Regency. This research is a qualitative descriptive research, which is based on an explanation of the numbers. The data in this study are the target and realization of Land and Building Tax Revenue, as well as the target and realization of Regional Original Revenue (PAD) for Tangerang Regency for 4 (four) years. The results showed that the level of effectiveness of PBB in 2018 to 2021 with the highest level of effectiveness was 121.28% in 2019 with very effective effectiveness criteria, in 2020 it was 115.67% with very effective criteria and the lowest level of effectiveness occurred in 2021 of 41.94% with Ineffective criteria. For the level of PBB contribution to Regional Original Income (PAD), it shows that in 2018-2021 the level of contribution is in the poor category. In 2018 it was 12.95% in the Poor category.